Crevettes pénéides récoltées dans l'océan Indien lors des campagnes Benthedi, Safari I et II, MD 32/Réunion - Crosnier, A. (Bull. Mus. Natn. Hist. nat., Paris, 1985)
Four deep-sea fishing expeditions conducted in the Indian ocean allowed to catch 31 species of penaeid shrimps. None of them is new but several of them were known only in geographic areas remote from the Indian ocean and they were often represented by a very small number of specimens which sometimes belonged only to one sex. Therefore, additional descriptions are given and they are based on a rather abundant illustration. Moreover, a few synonymies could be established by reexamination of various types.